IMPROVING STUDENTS’ LISTENING SKILL BY USING SONGS AS THE MATERIAL FOR SECOND GRADE STUDENTS OF MTsN MODEL PARE - Pratama, Ardi Sas (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 1 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
The objective of this study is to describe how songs influence the students’ achievement in listening English words. In constructing this study, the researcher collected data from the classroom action research, which was carried out through five activities. The activities were begun from selecting focus, collecting data, analyzing and interpreting the data, taking action and find out the students’ reflection. The subjects of this study were 35 students of second grade at MTsN Model Pare in the academic year 2014/2015. In doing this study, the researcher used an evaluation test which were gap filling and jumbled text as task designed in listening test and observation checklist. The data analysis of this study was descriptive qualitative and a bit of quantitative measurement to find the mean. Based on the data analysis from each activity, it can be seen that there is a significant difference of the students’ achievement in the first cycle and second cycle. The students’ achievement in the second cycle is higher than the first cycle. After the treatment by using songs in each cycle, the students’ achievement in listening English words improved. Based on this study, it is found that the use of songs in teaching English is effective. Likewise, it is suggested that songs in teaching English can be used for the English teachers. To get a wider generalization, research of similar kind should be done with different subjects.